Phylogenetic hypotheses, taxa and nomina in zoology - Dubois, Alain (Zootaxa, 2008)
Taxonomic paradigms have changed several times during the history of taxonomy, yet a single nomenclatural system, socalled Linnaean, has remained in force all along. It is theory-free regarding taxonomy as it relies on ostensional allocation of nomina to taxa, rather than on intensional definitions of nomina (e.g., “phylogenetic definitions”). Nomina are not descriptions, definitions or theories but simple labels designating taxa. Both for theoretical and practical reasons, this system should be maintained for the allocation and validity of nomina under a cladistic taxonomic paradigm. Whereas taxa can be cladistically defined by apognoses or cladognoses, nomina should remain attached to taxa through onomatophores, combined in some cases with a Principle of Coordination. Under such a system, the allocation of nomina to taxa is automatic, unambiguous and universal, and nomenclature does not infringe upon taxonomic freedom. However, to avoid misunderstandings and to solve some current problems, the current Code of zoological nomenclature should be improved in several respects. The distinction should be made clear between taxonomic categories, which have biological definitions, and nomenclatural ranks, which do not, as they give only a position in a nomenclatural hierarchy: if used consistently under a cladistic paradigm, they simply allow to express hypotheses about successive branchings and sistertaxa relationships. Taxa referred to a given rank in different groups cannot therefore be considered equivalent by any biological criterion. The nomenclatural rules should cover the whole taxonomic hierarchy, which is currently not the case in zoology. The recent strong increase in the number of higher taxa which results from cladistic analyses may quickly lead to chaos and problems in communication if the nomina of these taxa continue to be based on personal tastes and opinions. There is an urgent need for the zoological Code to cover these nomina with automatic and stringent rules leaving no place to subjective interpretation. Just like for those currently covered by the Code, the status of these nomina should be established in their first publication (nomenclatural founder effect). The Code should be protected against alternative nomenclatural systems by rejecting as unavailable all nomina and nomenclatural acts published without respecting the basic Linnaean system of nomenclatural hierarchy of ranks.